Analysis of modern development trends in the construction sector - Abasova, A.; Mamedov, E.; Абасова, А. А.; Мамедов, Е. Р. (Харківський національний автомобільно-дорожній університет, 2025)
The construction industry is undergoing significant transformations driven by advancements in technology, shifts in design and construction methodologies, and growing attention to sustainability. These changes are focused on improving efficiency, productivity, safety, and environmental responsibility. Key technological innovations, such as Building Information Modeling (BIM), automation, and the Internet of Things (IoT), are reshaping traditional construction methods by enhancing project planning, management, and execution. Additionally, sustainability practices, including the use of renewable materials and energy-efficient designs, are becoming essential in responding to both regulatory pressures and environmental concerns. The integration of mobile technologies, augmented and virtual reality (AR/VR), and cybersecurity measures is further revolutionizing the sector, enabling real-time communication, improving safety, and protecting sensitive data. These trends are not only enhancing construction processes but also providing a competitive edge to companies by promoting cost efficiency and faster project completion. As the industry embraces digitalization and green practices, it faces the challenge of overcoming barriers such as data management issues, cybersecurity concerns, and the need for employee training. The future of construction hinges on successfully integrating these technological advancements while ensuring compliance with industry standards and regulations. By adopting these innovations, the construction industry can enhance its long-term viability, contribute to sustainable development, and meet the growing demand for eco-friendly and technologically advanced infrastructure solutions.
Аналіз сучасних тенденцій розвитку будівельного сектора
Keywords: modern construction industry; competitiveness; construction sector; manage¬ment; information technologies; sustainability; innovation; сучасна будівельна індустрія; конкурентоспроможність; будівель¬ний сектор; управління; інформаційні технології; сталий розвиток; інновації; 69.003.13; 10.30977/ЕТК.2225-2304.2025.45.184